Liver transplantation for alveolar echinococcosis in an endemic region. Issue 8 (August 2015) - Aydinli, Bulent; Ozturk, Gurkan; Arslan, Sukru; Kantarci, Mecit; Tan, Onder; Ahıskalioglu, Ali; Özden, Kemalettin; Colak, Abdurrahim
<x xml:space="preserve">Abstract</x> Alveolar echinococcosis (AE) is a chronic disease caused by ingestion of the eggs of the parasitic cestode Echinococcosis multilocularis (EM). In severe cases, liver transplantation (LT) may represent the only possibility of survival and cure. Patients undergoing LT associated with hepatic AE at our institution between April 2011 and October 2014 were investigated retrospectively. The clinical findings of the 27 patients who participated in the study were noted. Kaplan‐Meier and chi‐square tests were used to investigate the effect of these characteristics on survival and mortality. Living donor LT was performed on 20 patients (74.1%), and deceased donor LT was performed on 7 patients (25.9%). Hilar invasion was the most common indication (14 patients, 51.9%) for transplantation. The patient follow‐up was 16.1 ± 11.4 months, and the overall survival rate was 77.8%. Primary nonfunction developed only in 2 patients in the posttransplantation period. Six patients died during monitoring, the most common cause of death being sepsis (3 patients). The relationship between the mortality rate of the patients and the invasion of the bile duct and/or portal vein by alveolar lesions was found to be statistically significant (P = 0.024 and P = 0.043, respectively). According to PNM staging, when the AE disease exceeds the resectability limits, the only alternative for the treatment of the disease is LT. However, different from LT due to cirrhosis, it is extremely difficult to perform a transplantation for AE disease because of the invasive characteristics of it. In order to decrease the difficulty of the operation and the postoperative mortality, the intracystic abscess and cholangitis which occur because of AE must be treated via medical and percutaneous methods before transplantation. Liver Transpl 21:1096‐1102, 2015. © 2015 AASLD.